Active behavior of abdominal wall muscles: Experimental results and numerical model formulation. (August 2016) - Grasa, J.; Sierra, M.; Lauzeral, N.; Muñoz, M.J.; Miana-Mena, F.J.; Calvo, B.
Abstract: In the present study a computational finite element technique is proposed to simulate the mechanical response of muscles in the abdominal wall. This technique considers the active behavior of the tissue taking into account both collagen and muscle fiber directions. In an attempt to obtain the computational response as close as possible to real muscles, the parameters needed to adjust the mathematical formulation were determined from in vitro experimental tests. Experiments were conducted on male New Zealand White rabbits ( 2047 ± 34 g ) and the active properties of three different muscles: Rectus Abdominis, External Oblique and multi-layered samples formed by three muscles ( External Oblique, Internal Oblique, and Transversus Abdominis ) were characterized. The parameters obtained for each muscle were incorporated into a finite strain formulation to simulate active behavior of muscles incorporating the anisotropy of the tissue. The results show the potential of the model to predict the anisotropic behavior of the tissue associated to fibers and how this influences on the strain, stress and generated force during an isometric contraction.